Structural uterine anomalies in recurrent pregnancy loss - Habib, Rizwana; Mufti, Asma Hassan; Wani, Nasir Jeelani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To determine frequency of different structural uterine anomalies in patients with recurrent pregnancy loss. Methods: This observational study was conducted over a period of one and half year at a tertiary care Hospital, included 40 women with recurrent pregnancy loss who underwent combined laparoscopy and hysteroscopy. Results: Twenty-eight patients (70%) had 3 episodes of miscarriage, eight patients (20%) had experienced 4 abortions and three patients (7.5%) had five abortions. Only one patient (2.5%) had six abortions. 32.5% patients had normal hysteroscopy while as 65% patients had no abnormal finding on laparoscopy. Hysteroscopy was abnormal in 67.5% patients with uterine septum (25%) being the most common finding followed by submucous myoma(20%), polyp (12.5%), cervical incompetence (7.5%) and intra uterine adhesions (2.5%). Laparoscopy was abnormal in 35% patients with endometriosis(17.5%) being the most common finding followed by intra pelvic adhesions (15%) and bicornuate uterus (2.5%). Conclusions: Women with recurrent pregnancy loss have increased association with structural uterine anomalies than general population. Both congenital and acquired uterine anomalies are associated with recurrent abortions.